Capacitating Agricultural Smallholders with Climate Advisories and Insurance Development (CASCAID-II): 2019 West Africa partners meeting proceedings - Sibiry Traoré, Pierre C.; MacCarthy, Dilys Sefakor; Faye, Aliou (2019)
CASCAID-II aims to reduce agricultural investment risk from smallholder farm to whole value chains to improve agricultural productivity and food security together with the profitability of agricultural enterprises, in a context of increasing smallholder integration in urban-driven markets. The 2019 West Africa partners meeting was organized to develop a common understanding and agreement on the project goals and approach to de-risking smallholder value chains in West Africa, and to discuss an operational set of priority research questions addressable within that approach. This document describes the priority value chain and R&D activities identified during the meeting and the articulation of sustainable intensification and risk management goals inside a single, actionable theory of change.